Putin's Political Regime and Its Alternatives. Issue 2 (4th March 2018) - Lukin, Alexander
Abstract: The article analyses the current Russian regime and its possible alternatives, both nationalist and pro-Western, from the viewpoint of various theoretical approaches. It argues that applying the criteria and terminology of political science, which are usually used in studies of modern Western societies, to define contemporary Russia's social and economic system is just as pointless as describing its political system in terms of the modern Western political system. It further states that to achieve an economic breakthrough, the Russian leadership will have to move towards: developing state institutions that are governed by the rule of law; the separation of powers; the restoration of self-government; and the creation of favourable conditions for, primarily, small and medium-size businesses.